Improving Acetic Acid Production by Over-Expressing PQQ-ADH in Acetobacter pasteurianus - Wu, Xuefeng; Yao, Hongli; Cao, Lili; Zheng, Zhi; Chen, Xiaoju; Zhang, Min; Wei, Zhaojun; Cheng, Jieshun; Jiang, Shaotong; Pan, Lijun; Li, Xingjiang (Frontiers in Microbiology, 2017)
Pyrroquinoline quinone-dependent alcohol dehydrogenase (PQQ-ADH) is a key enzyme in the ethanol oxidase respiratory chain of acetic acid bacteria. To investigate the effect of PQQ-ADH on acetic acid production by Acetobacter pasteurianus JST-S, subunits I (adhA) and II (adhB) of PQQ-ADH were over-expressed, the fermentation parameters and the metabolic flux analysis were compared in the engineered strain and the original one. The acetic acid production was improved by the engineered strain (61.42 g L-1) while the residual ethanol content (4.18 g L-1) was decreased. Analysis of 2D maps indicated that 19 proteins were differently expressed between the two strains; of these, 17 were identified and analyzed by mass spectrometry and two-dimensional gel electrophoresis. With further investigation of metabolic flux analysis of the pathway from ethanol and glucose, the results reveal that over-expression of PQQ-ADH is an effective way to improve the ethanol oxidation respiratory chain pathway and these can offer theoretical references for potential mechanism of metabolic regulation in acetic acid bacteria and researches with its acetic acid resistance.